Discrepancies in internal and external training load measurements during low-intensity biathlon training - Kårström, Andreas; Swarén, Mikael; Björklund, Glenn (Frontiers in Sports and Active Living, 2024)
Purpose: This study aimed to differentiate external and internal training loads during on-snow biathlon training by adding an accelerometer-derived metric. Methods: Eleven adolescent athletes were fitted with a combined heart rate (HR) and accelerometer to be worn during all training sessions. Duration, HR, training impulse (TRIMP), and average net force (𝐴𝑣𝐹 𝑁𝑒𝑡 ) were used as training variables. All training was divided into either low-intensity training (LIT), or high-intensity training (HIT) based on reported intensity. The training was further categorized as training without any shooting practice (NS) or as a combination of skiing and shooting (COMB). Duration, HR, TRIMP, and 𝐴𝑣𝐹 𝑁𝑒𝑡 were analyzed in a linear mixed model for the different training modalities. Results: All training was similar in duration for LIT and HIT sessions (p =.0521) and NS and COMB sessions (p =.988). TRIMP did not differentiate between LIT or HIT training (p =.350) or for NS compared to COMB (p =.298). While 𝐴𝑣𝐹 𝑁𝑒𝑡 decreased during COMB compared to NS during LIT sessions (p <.001) it remained similar during HIT training (p =1.00). Conclusion:. The study's findings indicated that there were no notable differences in internal training load (TRIMP) when comparing various training intensities and modes. However, the type of training had a significant impact on 𝐴𝑣𝐹 𝑁𝑒𝑡 , especially leading to a decrease during COMB sessions under LIT conditions. Incorporating an external load metric could offer a fresh approach when prescribing and evaluating training, providing deeper insights into the training load Ändrad fältkod